IMPLEMENTASI ALGORITMA FRAKTAL UNTUK KOMPRESI CITRA DENGAN METODE PENCARIAN LOKAL - Jatmika Jatmika; Tresia F Randongkir (Universitas Kristen Duta Wacana, 2013)
The nature of image compression methods always fall between lossy and lossless compression. Lossy compression eliminates insignificant information while retaining the perception, while lossless compression retains the original data completely. These recent years saw the rise of Fractal Image Compression (FIC), a new lossy image compression algorithm. This algorithm features a self-similarity, which in other word it regards an image as an arrangement of copied parts of the image itself, thus we only need a composition of transformation to code an image. This paper discuss about how fractal algorithm can be applied for image compression, how Fractal Image Compression works, and how to implement it using local search where comparison is done to the nearest area (segments) only. Searching in progress often involves great amount of data which takes a considerable time. Local search can reduce the time by comparing only the nearest area within the neighbourhood of the current block, which in turn shortened the overall processing time. However, the sharply reduced processing time achieved by localizing the search does not drastically reduce the quality of the output time.